FACTORS INFLUENCING FEMALE YOUTH PARTICIPATION IN AGRICULTURAL LIVELIHOOD GENERATING ACTIVITIES FOR SELF-CARE IN GWAGWALADA AREA COUNCIL, ABUJA, NIGERIA - Fidelis, Dutse; Shehu, Abbas; Yohanna Michael, Hannatu; Ezrah Bako, Danladi (Applied Studies in Agribusiness and Commerce, 2025)
This study examines female youth participation in agricultural livelihood generating activities for self-care in Gwagwalada Area Council, Abuja. The objectives were to: examine the extent of female youth participation in agricultural livelihood generating activities and the income generated, determine the levels of female youth self-care responsibilities and perceived contribution of participation in agricultural livelihood activities on their wellbeing, determine factors influencing female youth participation in agricultural livelihood activities in the study area. A multistage sampling procedure was used to select 133 female youths from 13 registered youth associations. Structured questionnaire was used to collect data while descriptive statistics and Logit regression model were used to analyze the data. The results showed that 30.1% of the respondents were engaged in crop production and generated an average income of ₦420,093.02 while only 3.0% were engaged in crop produce processing and generated ₦29,250.74. Also, almost half (47.4) of them spent money to take care of themselves of between 3-4 self-care responsibilities and about 41.5 spent an average of 130,078.95 on food per day. It also showed The logit regression results indicated that factors influencing female youth participation in agricultural livelihood generating activities include age, educational status, household size, income, occupation, and distance. While the study indicates that a significant portion of female youths is engaged in crop and poultry production, their overall participation in agricultural activities is limited. The study provides critical insights into the potential of agriculture as a viable solution to youth unemployment and is an instrument of female vulnerability reduction in Nigeria. The study recommends implementing policies to improve land access for female youths, including land reform initiatives that prioritize youth ownership and leasing options. Additionally, it suggests exploring strategies to reduce production costs through input subsidies, partnerships with agricultural suppliers, and community-based resource-sharing initiatives.